THE POTENTIAL OF DIGITAL MARKETING IN THE PROMOTION OF ORGANIC AGRICULTURAL PRODUCTS - Miloš Stojanović; Jasmina Gligorijević; Marina Grubor; Milica Popović; Biljana Ćorić; Darko Zarev; Miodrag Šmelcerović (Ekonomika Poljoprivrede (1979), 2024)
Organic agricultural production as a holistic approach that aims to promote food production without the use of synthetic chemical fertilizers, pesticides, genetically modified organisms and the system of food production and use takes place in accordance with the principles of preserving biodiversity, soil and ecosystems. However, this system of agricultural production incurs significantly higher costs, and the price of organic agricultural products comes also at a high cost. In addition to the price, one of the most important aspects of acceptance of organic agricultural products by consumers is environmental awareness. The aim of this paper is to analyze the potential for the improvement of digital marketing channels for the promotion of organic agricultural products. The factor analysis applied in this paper has shown that advertising through digital marketing channels has the potential to boost sales, according to producers of organic agricultural products in the Republic of Serbia.